Interest rate capping and the determinants of growth of non-deposit taking microfinance institutions in Kenya - Mutwiri, Josphine (Strathmore University, 2021)
There has been an unprecedented emergence and growth of Non-Deposit Taking Microfinance (credit only) institutions in Kenya in since 2003. The coming into effect of the interest capping law in September 2016 has seen most of the commercial banks become risk averse. Therefore, this study sought to analyses the effects of interest rate capping and the determinants of growth of non-deposit taking microfinance institutions in Kenya. The study was guided by the following specific objectives: to investigate the effect of loan officer expertise on growth of non-deposit taking microfinance business in Kenya; to examine the effect of customer service on growth of non-deposit taking microfinance business in Kenya; to establish the effect of products offered on growth of non-deposit taking microfinance business in Kenya and to determine the moderating effects of interest rate capping on the determinants of non-deposit taking microfinance business growth in Kenya. The study adopted a descriptive survey research design and it targeted 12 non-deposit taking MFIs in Nairobi where 102 operations managers were the respondents. A census was adopted because the target population could easily be accessed within Nairobi. The study collected primary data using questionnaires and the analysis of the collected data was done using means, standard deviation and regression analysis. The results were presented through tables and figures. From the results, all the variables (loan officer’s experience, customer service offered and the products offered and interest rate capping) were significant determinants of growth of non-deposit taking microfinance institutions in Kenya. The study concludes that while loan officer’s experience, customer service offered and the products offered all have positive and significant effect on growth of non-deposit MFUIs, interest capping regulation significantly moderates this relationship. The study recommends that the management of the non-deposit taking MFIs should high and recruit high qualified loan officers based on their level of education. The employees of the MFIs should be more creative and innovative with high adherence to work related ethics. Market research should be utilized in ensuring that the products offered to customers by the MFIs are easy to maintain and use. The Central Bank of Kenya (CBK) should work closely with the parliament in formulation of laws that would enhance the growth of MFIs like the interest rate capping.
A Thesis submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Business Administration at Strathmore University Business School
Keywords: Interest rate capping; Non-deposit taking microfinance institutions_Kenya; Central Bank of Kenya (CBK)